Risk factors, prognostic factors, and nomograms for liver metastasis in stage Tis-T2 colorectal cancer patients from a population-based study - Zejin Lin; Zeyu Lin; Taijun Yi; Yongling Liang; Ziyan Mai; Xingyu Li; Chengrui Zhong; Yunle Wan; Guolin Li (Scientific Reports)
Abstract Liver metastasis(LM) is the primary cause of mortality in patients with colorectal cancer. The incidence of liver metastasis in patients with stage Tis-T2 colorectal cancer is uncommon, and there is limited research available. While nomograms have been increasingly utilized in oncology, there is a lack of studies focusing on the diagnosis and prognostic assessment of liver metastasis in patients with stage Tis-T2 colorectal cancer. The data of patients with stage Tis-T2 colorectal cancer diagnosed between 2010 and 2015 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. Univariate and multivariate logistic regression analyses were conducted to identify the independent risk factors for liver metastasis in patients with stage Tis-T2 colorectal cancer. Additionally, both univariate and multivariate Cox proportional hazards regression analyses were performed to determine the independent prognostic factors in patients with stage Tis-T2 colorectal cancer who had liver metastasis. Subsequently, two nomograms were developed and the results were assessed using receiver operating characteristic (ROC) curves, calibration curves, and decision curve analysis (DCA). A total of 11,116 patients diagnosed with stage Tis-T2 colorectal cancer were studied, among whom 190 (1.71%) developed liver metastasis. The identified independent risk factors for liver metastasis in these patients included age, sex, primary tumor size, serum CEA levels, N stage, and histological type. Furthermore, sex, race, primary tumor size, serum CEA levels, and chemotherapy were found to be independent factors influencing the prognosis of patients with stage Tis-T2 colorectal cancer who developed liver metastasis. The accuracy of predicting the risk and prognosis of liver metastasis in these patients was confirmed through various analyses such as ROC curves, calibration curves, DCA curves, and Kaplan-Meier survival curves on both training and validation sets using two nomograms. The two nomograms are considered effective tools for predicting the risk of liver metastasis in patients with stage Tis-T2 colorectal cancer, as well as predicting the prognosis of patients with liver metastasis. These tools can aid in clinical decision-making.